1999
DOI: 10.1530/eje.0.1410409
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of protein kinase A catalytic subunit in thyroid adenomas and pituitary tumours

Abstract: Objective: The adenylyl cyclase system plays an important role in the control of both thyroid follicular and anterior pituitary cell function. Activating mutations affecting important pathway components such as the TSH receptor and Gsa occur in the majority of autonomously functioning thyroid nodules. Only a small proportion of other types of thyroid tumours, however, have been reported to harbour these mutations. Activating mutations of Gsa have been reported to occur in up to 40% of pituitary somatotroph ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…In this case, the R2B/ Ca ratio would favor an increased PKA activity. Esapa et al also observed that an alteration of the catalytic subunit of PKA is detected neither in thyroid tumors nor in pituitary adenomas (34). The tendency for a decreased level of R2A and R1A proteins in the ACA-S2 group might also take part in this stimulation of basal PKA activity.…”
Section: European Journal Of Endocrinology (2008) 158mentioning
confidence: 96%
“…In this case, the R2B/ Ca ratio would favor an increased PKA activity. Esapa et al also observed that an alteration of the catalytic subunit of PKA is detected neither in thyroid tumors nor in pituitary adenomas (34). The tendency for a decreased level of R2A and R1A proteins in the ACA-S2 group might also take part in this stimulation of basal PKA activity.…”
Section: European Journal Of Endocrinology (2008) 158mentioning
confidence: 96%
“…A part of area including codon 196 of the PKA gene was amplified using primers and PCR conditions as described by Esapa and Harris [9].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…PKA consists of two regulatory (R) and two catalytic (C) subunits. When two cAMP molecules bind to the R subunit, active C subunits are released and enter the nucleus where they phosphorylate CREB, which is involved in the transcription regulation process [7,9]. Therefore, both thyroid growth and function are regulated by cAMP-PI 3 [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations